DIURNAL VARIATION IN THE CATCHES OF SILVERBELLIES IN PALK BAY - Venkataraman, G; Badrudeen, M (Indian Journal of Fisheries, 2011)
5 comparison of the trawl landings from Palk Bay by day and night fishing showed a marked variation in the catches of silverbellies between the two. Another interesting feature noted was that even in night fishing, usually higher catches of silverbellies were observed on full moon nights than on new moon nights both in Palk Bay and Gulf of Mannar. From an analysis of the size groups of Leiognathus jonesi and L. brevirostris caught, it was seen that the proportion of smaller size group was greater in the night catches than in the day catches whereas the proportion of the larger size group was greater in the day catches than in the night catches. The diurnal variation in the catches of silverbellies shows that they stay at the bottom during day time and at nights good many of them migrate from there and rise to surface and sub-surface waters. This and the instances of sharp difference in the catch rates observed between full moon and new moon nights indicate a close link between light and the process of migration in silverbellies. The probable cause for the variation in the size groups in the catches by day and night fishing is pointed out. Fishing at the surface, sub-surface and midwater levels at night by using suitable gear is suggested for augmenting the production of silverbellies.